The Influence of School Principal Leadership on Teacher Performance in Private Vocational Schools in Biak Numfor Regency, Papua Province - Mataputun, Yulius; Mahdi, Mahdi (Journal of World Science, 2024)
Achieving national education goals heavily relies on the effectiveness of teachers, who serve as the cornerstone of educational excellence. However, the variance in teacher performance remains a challenge, necessitating exploration into influential factors. Among these, principal leadership emerges as a significant determinant. This study endeavors to examine the influence of principal leadership on teacher performance within private vocational schools in Biak Numfor Regency, Papua Province. Employing a quantitative correlational approach, data was collected from 115 teachers through questionnaires and document analysis. Utilizing simple linear regression, the analysis revealed a substantial positive correlation between principal leadership and teacher performance, accounting for 31.4% of the variance. The findings underscore the pivotal role of principal leadership in enhancing teacher performance, underscoring the imperative for cultivating effective leadership within educational institutions. These insights hold profound implications for educational policymakers, administrators, and stakeholders, emphasizing the need for targeted interventions to bolster leadership capabilities and thereby elevate overall educational outcomes.